Utilizing aqua play to children with attention deficit hyperactivity disorder - Valdepeñas, Marian Christine P. (College of Education, University of the Philippines Diliman, 2007)
Play is an integral part of human development. This experimental study utilized aqua play with attention deficit hyperactivity disorder (ADHD). It involved a 2-group pretest and posttest design comprising of 10 male students with ADHD whose ages ranged between 7 to 9 years old. The study was conducted in 2 private schools in Quezon City. Instruments used include NEW SNAP (SWANSON scale) rating scale, manual on aqua play, preliminary survey questionnaire, researcher's journal and research assistant's log. It was confirmed that aqua play significantly decreases inattention, hyperactivity and impulsivity of male students diagnosed with ADHD, that aqua play improved their behavior, and that aqua play can be used as an alternative form of teaching students with ADHD.